2016
DOI: 10.1159/000447702
|View full text |Cite
|
Sign up to set email alerts
|

Do Bioimpedance Measurements of Over-Hydration Accurately Reflect Post-Haemodialysis Weight Changes?

Abstract: Introduction: Bioelectrical impedance spectroscopy (BIS) devices are being used to determine ultrafiltration requirements to achieve target weight for haemodialysis (HD) patients. Pre-dialysis measurements are more convenient for both patients and staff. We wished to compare the changes in pre- and post-dialysis hydration measured by BIS with actual weight loss. Methods: We compared paired BIS measurements made pre and post HD using a BIS device based on a 3-compartmental model, designed to provide information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 87%
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 87%
“…Patients with pacemakers, and other implantable cardiac devices, and those unable to stand to measure bioimpedance were excluded from the study. Measurements were performed in a standardized manner, after the mid‐week haemodialysis session, allowing appropriate time for redistribution of fluid between body compartments post‐dialysis . Previous studies have validated this device against dual electron X ray absorptiometry .…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were performed in a standardized manner, after the mid-week haemodialysis session, 17,18 allowing appropriate time for redistribution of fluid between body compartments post-dialysis. 19,20 Previous studies have validated this device against dual electron X ray absorptiometry. 21 Lean body mass index (LBMI) and fat mass index (FMI) were calculated by lean body mass (LBM) and fat mass (FM) divided by height squared, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1 In clinical practice, Body Composition Monitor ® measurements are made pre-HD due to its important role in the estimation of dry weight as well as extracellular excess fluid. 13,14 Bioimpedance spectroscopy offers reliable assessments of body composition and several studies 15,16 report body composition measurements made before the HD session. 15 Although some authors suggest that the measurement should be made after HD, these studies evaluated the differences in body composition, pre-and post-HD.…”
Section: Discussionmentioning
confidence: 99%